DNA barcodes : methods and protocols - Kress, W. John; Erickson, David L. (Biologist) (New York : Humana Press/Springer, 2012)
A DNA barcode in its simplest definition is one or more short gene sequences taken from a standardized portion of the genome that is used to identify species through reference to DNA sequence libraries or databases. In DNA Barcodes: Methods and Protocols expert researchers in the field detail many of the methods which are now commonly used with DNA barcodes. These methods include the latest information on techniques for generating, applying, and analyzing DNA barcodes across the Tree of Life including animals, fungi, protists, algae, and plants. Written in the highly successful Methods in Molecular Biology series format, the chapters include the kind of detailed description and implementation advice that is crucial for getting optimal results in the laboratory. Thorough and intuitive, DNA Barcodes: Methods and Protocols aids scientists in continuing to study methods from wet-lab protocols, statistical, and ecological analyses along with guides to future, large-scale collections campaigns.
DNA barcodes : methods and protocols / W. John Kress and David L. Erickson -- Introduction to animal DNA barcoding protocols / Lee A. Weigt ... [and others] -- DNA barcodes for insects / John James Wilson -- DNA barcoding methods for invertebrates / Nathaniel Evans and Gustav Paulay -- DNA barcoding amphibians and reptiles / Miguel Vences ... [and others] -- DNA barcoding fishes / Lee A. Weigt -- DNA barcoding birds : from field collection to data analysis / Dario A. Lijtmaer ... [and others] -- DNA barcoding in mammals / Natalia V. Ivanova, Elizabeth L. Clare, and Alex V. Borisenko -- Methods for DNA barcoding of fungi / Ursula Eberhardt -- Methods for DNA barcoding photosynthetic protists emphasizing the macroalgae and diatoms / Gary W. Saunders and Daniel C. McDevit -- DNA barcoding methods for land plants / Aron J. Fazekas ... [and others] -- Field information management systems for DNA barcoding / John Deck ... [and others] -- Laboratory information management systems for DNA barcoding / Meaghan Parker ... [and others] -- DNA extraction, preservation, and amplification / Thomas Knebelsberger and Isabella Stoger -- DNA mini-barcodes / Mehrdad Hajibabaei and Charly McKenna -- Ways to mix multiple PCR amplicons into single 454 run for DNA barcoding / Ryuji J. Machida and Nancy Knowlton -- Practical evaluation of DNA barcode efficacy / John L. Spouge and Leonardo Marino-Ramirez -- Plant DNA Barcodes, Taxonomic Management and Species Discovery in Tropical Forests / Christopher W. Dick and Campbell O. Webb -- Construction and Analysis of Phylogenetic Trees Using DNA Barcode Data / David L. Erickson and Amy C. Driskell -- Phylogenetic analyses of ecological communities using DNA barcode data / Nathan G. Swenson -- FISH-BOL, a case study for DNA barcodes / Robert D. Ward -- Generating plant DNA barcodes for trees in long-term forest dynamics plots / W. John Kress, Ida C. Lopez, and David L. Erickson -- Future directions / David L. Erickson and W. John Kress.
Includes bibliographical references and index.
Keywords: Genetic markers; DNA data banks; DNA Barcoding, Taxonomic -- Laboratory Manuals; Data Mining -- methods -- Laboratory Manuals